1981
DOI: 10.1073/pnas.78.11.6567
|View full text |Cite
|
Sign up to set email alerts
|

Further perspectives on the charge transfer transitions of blue copper proteins and the ligand moieties in stellacyanin

Abstract: The charge transfer spectra of plastocyanin and azurin are analyzed in detail, taking into account the structural information that is available. The number and relative energies ofthe low-lying charge transfer bands attributable to cysteine and methionine sulfur are considered with reference to the energy levels associated with the donor centers and to experimental work on relevant complexes. Two cysteine -*Cu(fI) charge transfer transitions are assigned to bands that occur near 620 nm and near 770 nm. Energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Multiple (strong and weak) Au binding sites in BSA has also been suggested by others . A plausible origin of the red fluorophore could involve, ligand field (LF), ligand-to-metal charge transfer (LMCT), and/or metal-to-ligand charge transfer (MLCT) transition, although the details of the local coordination at the Cys–Cys binding sites are needed to understand the mechanism. Alternatively, strong electron delocalization can occur at aromatic residue(s) among at least one of the Sites I – IX , for example via dehydration or cyclization. However, it is unclear whether such processes can be mediated by Au­(III).…”
Section: Resultsmentioning
confidence: 86%
“…Multiple (strong and weak) Au binding sites in BSA has also been suggested by others . A plausible origin of the red fluorophore could involve, ligand field (LF), ligand-to-metal charge transfer (LMCT), and/or metal-to-ligand charge transfer (MLCT) transition, although the details of the local coordination at the Cys–Cys binding sites are needed to understand the mechanism. Alternatively, strong electron delocalization can occur at aromatic residue(s) among at least one of the Sites I – IX , for example via dehydration or cyclization. However, it is unclear whether such processes can be mediated by Au­(III).…”
Section: Resultsmentioning
confidence: 86%
“…8 the low temperature (T--20 K) visible spectrum is reported, together with the fitting in terms of Gaussian components. Four bands, attributed to ligand to metal charge transfer transitions, are expected (Solomon et al 1980;McMillin and Morris 1981;Gewirth and Solomon 1988) and, indeed, four Gaussian components (labeled I to IV in Fig. 8) are needed to fit the spectrum.…”
Section: H(v) C 2 H(v) Mg=acoth~+mentioning
confidence: 99%
“…St however lacks this amino acid. On the basis of spectral analysis, McMillin and co-workers (Tennent & McMillin, 1979;McMillin & Morris, 1981) have therefore suggested that the fourth ligand in stellacyanin may be a disulfide sulfur. A similar suggestion has been made by Ferris et al (1978), who analyzed the resonance Raman spectra of stellacyanin.…”
Section: Resultsmentioning
confidence: 99%